โซฟอสบูเวียร์: ข้อมูลปัจจุบันในการรักษาโรคติดเชื้อไวรัสตับอักเสบซีเรื้อรัง (SOFOSBUVIR: CURRENT INFORMATION FOR CHRONIC HEPATITIS C TREATMENT) - Tewthanom, Karunrat (Thai Bulletin of Pharmaceutical Sciences, 2017)
โซฟอสบูเวียร์เป็นยาต้านไวรัสตับอักเสบซีซึ่งได้รับการรับรองจากองค์การอาหารและยาในการใช้รักษาภาวะตับอักเสบเรื้อรังจากเชื้อไวรัสตับอักเสบซีโดยใช้ร่วมกับยาขนานอื่นที่เป็นการรักษามาตรฐาน คือ อินเตอร์เฟอรอนและ ไรบาไวริน และการใช้ร่วมกับยาต้านไวรัสกลุ่มใหม่ที่ไม่ใช่อินเตอร์เฟอรอน จากคุณสมบัติยาที่มีโครงสร้างเป็น nucleotide analog ยับยั้ง HCV NS5B polymerase ทำให้การแบ่งตัวของไวรัสยุติลงและไม่มีการเพิ่มจำนวน ยาถูกดูดซึมได้เร็วโดยยาที่ดูดซึมจะเปลี่ยนเป็นเมแทบอไลต์ คือ GS-331007 ยามีค่าครึ่งชีวิต 0.4 ชั่วโมง ส่วนเมแทบอไลต์ มีค่าครึ่งชีวิต 27 ชั่วโมง กระบวนการขจัดยาคือ ยาจะเปลี่ยนเป็นเมแทบอไลต์และขจัดออกทางไตเป็นหลัก (เมแทบอไลต์ขับออกทางปัสสาวะร้อยละ 78) ไม่ต้องมีการปรับขนาดยาในผู้ป่วยโรคตับหรือไตบกพร่องน้อยถึงปานกลาง แต่ยังไม่มีการศึกษาในผู้ป่วยที่มีการทำงานของตับและไตบกพร่องรุนแรง จากการศึกษาทางคลินิกหลายการศึกษา ทำให้ยืนยันถึงประสิทธิภาพในการรักษาภาวะตับอักเสบจากเชื้อไวรัสตับอักเสบซี ทั้งการใช้ร่วมกับยาที่เป็นการรักษามาตรฐาน และการใช้ร่วมกับยาต้านไวรัสกลุ่มใหม่ สำหรับอาการไม่พึงประสงค์ที่พบบ่อยคือ อาการอ่อนแรง และส่วนใหญ่จะเป็นอาการไม่พึงประสงค์จากยาในสูตรที่ใช้ร่วมกัน อัตราการดื้อยาของยาโซฟอสบูเวียร์พบน้อยเพราะตำแหน่งเป้าหมายของยาจะเป็นส่วนที่ไวรัสค่อนข้างเปลี่ยนแปลงยาก เมื่อพิจารณาด้านอันตรกิริยาของยา เนื่องจากโซฟอสบูเวียร์เป็นสารที่จับกับ P-glycoprotein (P-gp) และ breast cancer resistance protein (BCRP) ดังนั้นยาที่กระตุ้นการทำงานของ P-gp ในลำไส้ (เช่น ไรแฟมฟิซิน หรือ St. John’s wort) อาจจะลดระดับความเข้มข้นของยาในเลือดได้ ทำให้ลดผลการรักษาเนื่องจากปริมาณยาในร่างกายน้อย ดังนั้นจึงไม่แนะนำให้รับประทานร่วมกับยาที่มีคุณสมบัติดังกล่าวจากข้อมูลคุณสมบัติของยาและการศึกษาทางคลินิกที่ผ่านมาจะเห็นว่า ยาโซฟอสบูเวียร์เป็นยาที่น่าสนที่จะใช้เป็นทางเลือกหนึ่งของการรักษาโรคตับอักเสบจากไวรัสซี โดยสามารถใช้ร่วมกับยาดั้งเดิมคืออินเตอร์เฟอรอนและไรบาไวรินหรือสามารถใช้ร่วมกับยาต้านไวรัสรุ่นใหม่กรณีที่ไม่สามารถใช้สูตรยาอินเตอร์เฟอรอนและยาไรบาไวริน นับเป็นการเพิ่มโอกาสการรักษาให้ผู้ป่วยโรคนี้ให้มีทางเลือกอื่นมากขึ้น Sofosbuvir, an anti-hepatitis C virus medication that approved from FDA in treatment chronic hepatitis C infection by combination with standard medication therapy; interferon and ribavirin, and combination with new non-interferon based anti-viral regimens. According to drugs’ properties, it is nucleotide analog that inhibits HCV NS5B polymerase then terminate the virus replication and no viral assembly. The drug is rapid absorbed and turn to be a metabolite; GS-331007. The drug’s half-life is 0.4 h, while the metabolite has half-life 27 h. The elimination is metabolism to active metabolite and excretion via kidney (the metabolite is excreted by kidney 78%). The dose adjustment is unnecessary in mild to moderate kidney and liver diseases but none of study in severe kidney and liver diseases population. Several studies confirmed efficacy in treatment of chronic hepatitis C virus infection, both concomitant with standard regimens or combination with non-interferon based regimens. The most common adverse effect is fatigue and usually come from combination drugs that use in standard regimens. Focus on adverse effects, the most adverse drug reaction is fatigue and usually comes from the combination drugs in treatment regimens. The resistance rate found low because the drug target is the invariable part of virus component. Consider for interaction issue, according to affinity in binding to P-glycoprotein (P-gp) and breast cancer resistance protein (BCRP), drugs that can activate P-gp in gastrointestinal tracts (example; Rifampicin or St. John’s wort) may decrease Sofosbuvir concentration in blood. Leading, treatment failure due to small amount of drug is in the body. Therefore, it is not recommended to administration Sofosbuvir with drugs that can activate P-gp. From the drug properties and information of previous clinical studies found that Sofosbuvir is an interesting drug to use as an alternative in treatment chronic hepatitis C infection. It can be able to use in combination with standard regimens (interferon and ribavirin) or use with non-interferon based regimens in case of interferon intolerance. These strategies give more alternative therapeutic options to the patients.